Conceptual Review on Efficacy of Visha Taila in the Management of Vicharchika (AYUSHDHARA, 2025)
Vicharchika (eczema), classified as Kshudra Kustha in Ayurveda, is a chronic skin disorder characterized by itching (Kandu), redness (Raga), discharge (Srava), and scaling (Pidika). The study explores the conceptual framework of treating Vicharchika through the application of Visha Tail, a polyherbal formulation. The formulation integrates potent herbs such as Tagar, Kaner, Vacha, Kustha, Aparajita, Manjistha, Haldi, Daruharidra, Arka, Vatsanabh, Gomutra, Sarshap, Chameli, Raktachandan, Nirgundi, and Saptaparna. Each herb possesses specific properties such as anti-inflammatory, antimicrobial, detoxifying, and blood-purifying effects. This synergistic approach targets the root cause by balancing aggravated Kapha and Pitta Doshas, alleviating symptoms, and promoting skin healing. The study concludes that Visha Taila offers a holistic and effective Ayurvedic intervention for managing Vicharchika, though clinical validation and standardization remain essential.